2022
DOI: 10.14309/ctg.0000000000000494
|View full text |Cite
|
Sign up to set email alerts
|

Limited dose-dependent effects of vedolizumab on various leukocyte subsets

Abstract: OBJECTIVES:The anti-α4β7 integrin antibody vedolizumab (VDZ) is successfully used for the treatment of inflammatory bowel diseases. However, only a subgroup of patients respond to therapy. VDZ is administered at a fixed dose, leading to a wide range of serum concentrations in patients. Previous work from our group showed a dose-dependent preferential binding of VDZ to effector compared with regulatory CD4+ T cells. Therefore, we aimed to determine the dose-dependent binding profile of VDZ to other leukocyte su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Specifically, our fluorescence microscopic analysis revealed both surface and intracellular vedo-800CW binding. In addition, consistent with recent findings 14,17,19 we found that vedolizumab binds to a variety of immune cell types, including plasma cells, macrophages, and eosinophils whereas an actual correlation between T cells and vedo-800CW was not observed. These findings support the hypothesis that T cell migration to the mucosa is prevented and that T cells are likely not the sole therapeutic target of vedolizumab.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Specifically, our fluorescence microscopic analysis revealed both surface and intracellular vedo-800CW binding. In addition, consistent with recent findings 14,17,19 we found that vedolizumab binds to a variety of immune cell types, including plasma cells, macrophages, and eosinophils whereas an actual correlation between T cells and vedo-800CW was not observed. These findings support the hypothesis that T cell migration to the mucosa is prevented and that T cells are likely not the sole therapeutic target of vedolizumab.…”
Section: Discussionsupporting
confidence: 92%
“…10,19 Here, we found intracellular localization of vedolizumab in both macrophages and eosinophils, consistent with previous studies showing an interaction between vedolizumab and α4β7expressing macrophages and eosinophils. 12,17,29 Although this interaction between vedolizumab and various immune cell types is well established, the consequences of this drug binding to different immune cell types remain poorly understood and require further study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are conflicting data regarding the primary mechanism of action of VDZ. VDZ has been reported to bind to CD4 T, CD8 T, B, NK, and granulocytes in the peripheral blood 51,52 . Here we confirm that VDZ shifts α 4 β 7 + cells from the colon to the circulation for most cell types, but this results in a small net change in tissue cell frequency for most cell subsets, apart from MNPs.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the data that we present in this manuscript shed a new light on etrolizumab, since we show that non‐classical monocytes are a target of the antibody. Although an impact of etrolizumab on innate immune cell subsets in general and non‐classical monocytes in special had to be concluded in analogy to what is known for vedolizumab, 27 , 39 , 40 , 41 these data are the first to show that this effect may go beyond vedolizumab due to the expression of αEβ7 by a fraction of these cells. Indeed, our functional analyses demonstrate that etrolizumab specifically impedes the adhesion of non‐classical monocytes not only to MAdCAM‐1, but also to E‐Cadherin.…”
Section: Discussionmentioning
confidence: 90%